Toward antiviral therapy/prophylaxis for rhinovirus‐induced exacerbations of chronic obstructive pulmonary disease: challenges, opportunities, and strategies. (21st September 2015) - Thibaut, Hendrik Jan; Lacroix, Céline; De Palma, Armando M.; Franco, David; Decramer, Mark; Neyts, Johan
Summary: Chronic obstructive pulmonary disease (COPD) is a life‐threatening lung illness characterized by persistent and progressive airflow limitation. Exacerbations of COPD contribute to the severity of this pathology and accelerate disease progression. To date, pharmacological treatment of both stable COPD patients and patients experiencing exacerbations is mainly symptomatic with bronchodilators and steroids as the mainstay of therapy. Bacteria trigger such exacerbations in a number of cases; hence, antibiotics might be included in the treatment as well. Several respiratory viruses are frequently detected in sputum from patients during COPD exacerbations. These include influenza viruses, respiratory syncytial virus, and, most often, rhinoviruses. In this review, we discuss the potential use of an anti‐rhinovirus drug for the treatment and prophylaxis of rhinovirus‐induced COPD exacerbations and the path forward toward the development and use of such a drug. Copyright © 2015 John Wiley & Sons, Ltd.